Assessing complex interventions: a systematic review of outcomes used in randomised controlled trials on STI partner notification in high-income countries - Victoire Sawras; Sylvie Deuffic-Burban; Marie Préau; Bruno Spire; Yazdan Yazdanpanah; Karen Champenois (BMC, 2023)
Abstract Background Partner notification interventions are complex and assessing their effectiveness is challenging. By reviewing the literature on the effectiveness of partner notification interventions, our aim was to evaluate the choice, collection, and interpretation of outcomes and their impact on study findings. Methods We conducted a systematic review of individual-level randomised controlled trials evaluating the effectiveness of partner notification interventions for bacterial STIs, HIV or sexually transmitted HCV in high-income countries since 2000. Partner notification interventions included assisted patient referral interventions and expedited treatment. The content analysis was carried out through a narrative review. Results In the 9 studies that met the inclusion criteria, 16 different outcomes were found. In most studies, one or two outcomes assessing partner notification practices were associated with an outcome reflecting STI circulation through index case reinfections. These outcomes assessed the main expected effects of partner notification interventions. However, partner notification is composed of a succession of actions between the intervention on the index case and the testing and/or treatment of the notified partners. Intermediate outcomes were missing so as to better understand levers and barriers throughout the process. Potential changes in participants' sexual behaviour after partner notification, e.g. condom use, were outcomes reported in only two studies assessing interventions including counselling. Most outcomes were collected through interviews, some weeks after the intervention, which might lead to desirability and attrition biases, respectively. Assessment of the effectiveness of partner notification interventions on partner testing/treatment was limited by the collection of data from index cases. Few data describing index cases and their partners were provided in the studies. Additional data on the number and type of exposed partners and the proportion of partners already aware of their infection before being notified would help to interpret the results. Conclusions These insights would help to understand why and under what conditions the intervention is considered effective and therefore can be replicated or adapted to other populations and contexts.